Public knowledge about oral cancer in Uganda: a free dental camp experience - Rose Chalo Nabirye; Adriane Kamulegeya (Journal of Health Research, 2019)
Purpose - The purpose of this paper is to assess the levels of awareness and knowledge about oral cancer, its causes and or risk factors among Ugandan patients seeking oral healthcare. Design/methodology/approach - This was a cross-sectional study on adult patients who attended a free dental camp. An assistant-administered questionnaire either in English or Luganda was provided to every even-numbered registered adult who consented to participate in the study. Information on demographics and known risk factors for oral cancer were captured. The two knowledge questions on oral cancers were scored by adding up all the correctly identified causes, non-causes and risk factors then scored out of the total. Data analysis was done by calculating proportions, Student’s’ t-tests and χ2 tests with significant p-value set at 0.05. Findings - The results showed a low level of awareness/knowledge about oral cancer in studied population. In total, 60 percent and less than 50 percent of respondents identified smoking and alcohol use as risk factors for oral cancer, respectively. Majority of respondents (88.8 percent) would seek help from medical personnel if diagnosed with oral cancer. Screening for cancer was low despite awareness and knowledge that it improves the chances of successful treatment. Research limitations/implications - Emphasis on risk factors including alcohol use in public health messages, use of mass media, religious and community leaders to disseminate messages to the communities and further research were recommended. Practical implications - We need to emphasize the role of alcohol in oral cancer causation just as we do for tobacco consumption. Originality/value - No study has been conducted in Uganda on the level of awareness yet the incidence of the disease and use of high-risk products are rising.